Reform of State Owned Enterprise and Public-Private Partnerships in Iraq - Rimmer, Stephen; Al-Ani, Mohammed (World Bank, Washington, DC, 2014)
While Iraq is a middle-income (IBRD) country it faces significant challenges which are commonly found in low income countries. Its economy also remains dependent on hydrocarbons and revenue from these resources generates over 95 percent of budget revenues. However, this sector employs only one per cent of the labor force. Iraq has significant infrastructure reconstruction and rehabilitation needs; and poorly performing regulatory policies, institutions and processes. Developing a strong and healthy private sector is necessary for Iraq to develop into a diversified and resilient market economy with rising living standards and sufficient jobs. In the meantime, Iraq's transition to a more diversified market economy continues to take place in a fragile political, security and institutional context. The Government has also requested support in implementing Public Private Partnerships (PPPs) in Iraq. The Bank has helped build a consensus among economic experts in the Government of Iraq that attracting international private sector investors and operators is critical to jumpstarting SOE reforms. Without such external support, the SOEs will lack the business and management expertise, as well as the access to capital which would allow them to restructure these firms into companies that could survive in the new Iraqi economy.